Die Mauer steht noch, oder: Begegnungen an der Grenze. Menschen, Geschichten und Konflikte in Unterleuten (2016) von Juli Zeh - Jurzysta, Aneta (Tematy i Konteksty, 2017)
The article is devoted to Juli Zeh’s novel Unterleuten, which explores what happens in a small village outside of Berlin, when an energy company arrives with plans to develop a wind farm. Brutality surfaces in many forms, from harassment and deliberate cruelty to perverse acts of revenge. Two old men, a successful agribusiness man and a displaced comrade from the former GDR farming collective, reengage in past conflicts, and their twenty-year-long feud grows into a prime source of vicious ill feeling. The structure of the novel is like a literary kaleidoscope: Unterleuten is a place between past and present, east and west, city and province, civilisation and tradition, reality and fiction, true and false, winners and losers.